Development of Intellectual Abilities of Primary School Students in Mathematics Lessons (Journal of Pedagogical Inventions and Practices, 2022)
The article discusses the features of the development of intellectual abilities of primary school students. Ways of developing mathematical abilities in mathematics lessons are revealed.